The Examination of the Specific Thermal Resistivity And Moisture of Cable Bed In Laboratory Conditions - Simić, Ninoslav P; Obradović, Stefan (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
In this paper firstly examples of changes of current maximum in dependence of the value of specific thermal resistivity of the soil ρz are briefly presented. Afterwards for two cases, sample of undisturbed soil from cable route and sample of specially prepared backfill cable bed material, using the method of coniferous probe the values of ρz are obtained. The difference is pointed out between the measured values of specific thermal resistivity and moisture of the samples that were being drained in thermal chambers and the samples that were being drained on ambient temperature. For drainage in thermal chambers, based on experience for cross-linked polyethylene cables, the temperatures of 60°C to 90°C were selected while in second case the temperature of 20°C over a long period of time was chosen. The obtained results were analyzed and shown through tables and graphs. At the end of this paper the moisture of the soil was calculated for sampled cable bed that corresponds to the value of ρz of 1(Km/W) and the proposition for composition of the cable bed that allows the projected value of the transmission power of the cable.